Commercialization of the Diacol capiro, Parda pastusa L. and amarilla potatoes´ variety - Figueroa N, Deisy; Rosas L, David; Torres M, Francisco (Revista de Ciencias Agrícolas, 2012)
This study was conducted in three of the districts most representative of the municipa- lity of Pasto (Catambuco, La Laguna and Santa Barbara), in terms of planting area and number of farmers engaged in three potato varieties most commonly grown and inten- ded for sale in the region (Diacol Capiro, Parda Pastusa and Amarilla). We studied va- riables that directly affect the marketing process, in terms of prices at the producer level, brokers, market places and supermarkets in the city of Pasto, determining marketing channels and margins, and later make recommendations that lead to improved product marketing in the region. Includes production and a diagnosis of social and technical characterization of the producers, reflecting the reality of the majority of farmers, in terms of gaps and the socio-economic benefits. The analysis of marketing channels and margins for the three varieties, concludes that there is a vast array of marketing for the potato, from the producer to the consumer. According to the results, the producer gets more participation (PP) in the marketing of potatoes Diacol Capiro and Parda Pastusa, on the contrary, in the Amarilla, variety retailers obtain larger gross margins on the market (GMM).